Growth Pattern of Thynnichthys thynnoides from The Kebun Nopi Lake Kuantan Mudik Subdistrict Kuantan Singingi Regency, Riau - Erwina Citra Sejati Gulo; Efawani Efawani; Ridwan Manda Putra (Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
Thynnichthys thynnoides is a freshwater fish found in Kebun Nopi Lake. This fish has economic value and is often caught by fishermen. A study aims to determine the growth pattern of T. thynnoides. The study used a survey method. Sampling was carried out 4 times from March-April 2022. The results showed that 107 fish captured consist of 39 females and 68 males. T. thynnoides from the Danau Kebun Nopi has TL 83-165 mm, SL 58-130 mm, HDL 18-30 and weight 5,61-42,04 gr. The meristic characteristic of the fish were as follow: D.I.8-10, P.10.4-7, V.1.7-8, A.1.5-7, C.2.16-18, 20-22 pre-dorsal fin scale, 44-48 around the body scale, 14-20 caudal peduncle scale and 57-60 lateral line scale. The relationship between length and weight of females showed positive allometric (b=3,26) and males showed negative allometric (b=2,62). The condition factors from 0,6854-1,2858 where females were generally in better condition than the males.